Appendiceal mixed adenoneuroendocrine carcinomas, a rare entity that can present as a Krukenberg tumor: case report and review of the literature. Issue 1 (December 2015) - Romeo, Margarita; Quer, Ariadna; Tarrats, Antoni; Molina, Carlos; Radua, Joaquim; Manzano, José-Luís
Abstract Background Mixed adenoneuroendocrine carcinoma is a rare tumor recently recognized as a new category in the last World Health Organization (WHO) classification of appendiceal tumors (2010). This term has been proposed to designate carcinomas of the appendix that arise by progression from a pre-existing goblet cell carcinoid. Mixed adenoneuroendocrine carcinomas are more aggressive tumors than typical goblet cell carcinoids and usually present with peritoneal spreading and ovarian masses. Staging, some histological features, and completeness of surgery are factors that determine its evolution. Case Presentation We report the case of a mixed adenoneuroendocrine carcinoma—signet ring cell subtype—that presented as a Krukenberg tumor of unknown primary. Conclusion The review of literature is focused on the most recent WHO pathologic classification of appendiceal tumors containing goblet cell clusters, which seems to correlate with prognosis. A management proposal for mixed adenoneuroendocrine carcinomas reported in previous literature is also discussed. This ranges from right hemicolectomy to cytoreduction plus hyperthermic intraperitoneal chemotherapy, in both cases usually followed by intravenous chemotherapy.